The effects of intraperitoneal CO2 insufflation on ETCO2 and blood gases during laparoscopic cholecystectomy - (:unkn) unknown (My University, 1996)
Objective: The aim of this prospective study was to examine the effects of intraperitoneal CO2 insufflation on ETCO2 and blood gases during laparoscopic cholecystectomies. Methods: Twenty patients ASA I, II, aged 20-65 years were studied. After induction, anesthesia was maintained with 1% isoflurane in 70% N20 and O2. Vecuronium bromide was administered for muscle relaxation and all patients were ventilated mechanically with 10 ml/kg tidal volume and 10/min respiratory rate. Mean arterial pressure, heart rate, ETCO2, SpO2 and peak airway pressure were measured before and after CO2 insufflation, at 5 minutes intervals and blood gases at 15 minutes intervals during operation. Results: The peak airway pressure and mean arterial pressure increased immediately after CO2 insufflation. ETCO2 increased significantly at 5th minute of CO2 insufflation. At 15th minute PaCO2 increased and pH decreased significantly. A plateau was reached ten minutes later and remained constant during operation. No significant differences were observed in O2 saturation, heart rate and PaO2 values. Conclusion: Intraperitoneal CO2 insufflation causes significant increases in ETCO2, PaCo2, peak airway pressure and decreases in pH.
Keywords: Blood gases; CO2 insufflation; End tidal carbondioxide; Hypercapnia; Laparoscopic cholecystectomy; Oxygen saturation